Ovarian cancer risk factors by tumor dominance, a surrogate for cell of origin. Issue 3 (13th March 2013) - Kotsopoulos, Joanne; Terry, Kathryn L.; Poole, Elizabeth M.; Rosner, Bernard; Murphy, Megan A.; Hecht, Jonathan L.; Crum, Christopher P.; Missmer, Stacey A.; Cramer, Daniel W.; Tworoger, Shelley S.
<x xml:space="preserve">Abstract</x> Differentiating ovarian tumors based on developmental pathway may further enhance our understanding of the disease. Traditionally, ovarian cancers were thought to arise from the ovarian surface epithelium; however, recent evidence suggests that some tumors originate in the fallopian tube. We classified cases in a population‐based case–control study (New England Case–Control [NECC] Study) and two cohort studies (Nurses' Health Study [NHS]/Nurses' Health Study II [NHSII]) by tumor dominance, a proxy for tissue of origin. Dominant tumors (likely ovarian origin) are restricted to one ovary or are at least twice as large on one ovary compared to the other. Ovarian cancer risk factors were evaluated in relation to dominant and nondominant tumors (likely tubal origin) using polytomous logistic regression (NECC) or competing risks Cox models (NHS/NHSII). Results were combined using random‐effects meta‐analyses. Among 1, 771 invasive epithelial ovarian cancer cases, we observed 1, 089 tumors with a dominant mass and 682 with no dominant mass. Dominant tumors were more likely to be mucinous, endometrioid or clear cell, whereas nondominant tumors were more likely to be serous. Tubal ligation, two or more births, endometriosis and age were more strongly associated with dominant tumors (rate ratio [RR] = 0.60, 0.83, 1.58 and 1.37, respectively) than nondominant tumors (RR = 1.03, 0.93, 0.84 and 1.14, respectively; p‐difference = 0.0001, 0.01, 0.0003 and 0.01, respectively). These data suggest that risk factors for tumors putatively arising from ovarian versus fallopian tube sites may differ; in particular, reproductive factors may be more important for ovarian‐derived tumors. As this is the first study to evaluate ovarian cancer risk factors by tumor dominance, these results need to be validated by other studies.